Exploring the Potential of Java Mountain Flora Collections as Interpretive Materials for Tourism at the Baturraden Botanical Garden - Fahriza Junizar; Shafira Hanindita (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
Baturraden Botanical Garden is an ex-situ conservation area that have crucial role in the preservation of Javanese mountain flora, particularly endemic species such as Nepenthes adrianii, Scutellaria slametensis, and Homalomena bellula. This research aimed to explore the potential of this flora collection as material for guided tours and to design an appropriate interpretation concept aligned with tourist characteristics. This research methodology employed a qualitative descriptive approach through interviews, observation, and literature review. The results indicate Baturraden Botanical Garden possesses 722 plant species arranged taxonomically and thematically. Tourists are predominantly from the 17–27 age group, consisting mainly of students who tend to favor educational activities. Therefore, the most suitable interpretation technique is direct interpretation through guided walk with an educational and interactive approach. The guiding material focuses on introducing endemic flora and conservation values to enhance environmental awareness. The main constraints in implementing interpretation include limited human resources and the absence of certified guides. Findings of this study affirm that flora collection holds significant potential as a medium for conservation education and as a reinforcement of the destination's image as a sustainable ecotourism destination.